Old bones - Preston, Douglas J; Child, Lincoln (Preston, Douglas J Nora Kelly, 2019)
Young curator Nora Kelly leads a team in search of the "Lost Camp" of the Donner Party, but as they expose the real truth of what happened, those ancient horrors lead to present-day violence in a case assigned to rookie FBI agent Corrie Swanson.